Arboreality increases reptile community resistance to disturbance from livestock grazing. Issue 2 (7th September 2017) - Neilly, Heather; Nordberg, Eric J.; VanDerWal, Jeremy; Schwarzkopf, Lin
Abstract: Domestic livestock grazing directly alters ground‐level habitat but its effects on arboreal habitat are poorly known. Similarly, the response to grazing of ground‐dwelling fauna has been examined, but there are few studies of arboreal fauna. Globally, grazing has been implicated in the decline of vertebrate fauna species, but some species appear resistant to the effects of grazing, either benefiting from the structural changes at ground level or avoiding them, as may be the case with arboreal species. Here, we examine arboreal and terrestrial habitat responses and reptile community responses to grazing, to determine whether arboreal reptile species are more resistant than terrestrial reptile species. We conducted arboreal and terrestrial reptile surveys on four different grazing treatments, at a 19‐year experimental grazing trial in northern Australia. To compare the grazing response of arboreal and terrestrial reptile assemblages, we used community, functional group and individual species‐level analyses. Species responses were modelled in relation to landscape‐scale and microhabitat variables. Arboreal reptile species were resistant to the impact of grazing, whereas terrestrial reptiles were negatively affected by heavy grazing. Terrestrial reptiles were positively associated with complex ground structures, which were greatly reduced in heavily grazed areas. Arboreal lizards responded positively to microhabitat features such as tree hollows. Synthesis and applications . Arboreal and terrestrial reptiles have different responses to the impact of livestock grazing. This has implications for rangeland management, particularly if management objectives include goals relating to conserving certain species or functional groups. Arboreal reptiles showed resistance in a landscape that is grazed, but where trees have not been cleared. We highlight the importance of retaining trees in rangelands for both terrestrial and arboreal microhabitats. Abstract : Arboreal and terrestrial reptiles have different responses to the impact of livestock grazing. This has implications for rangeland management, particularly if management objectives include goals relating to conserving certain species or functional groups. Arboreal reptiles showed resistance in a landscape that is grazed, but where trees have not been cleared. We highlight the importance of retaining trees in rangelands for both terrestrial and arboreal microhabitats.